Aplicação de Realidade Aumentada como meio de Promoção do Turismo e Poesia Portuense - Sandra Maria Amorim Pires (2023)
Augmented Reality is an emerging technology that allows the merging of the virtual and real world. In recent times, mobile platforms have also developed considerably, becoming capable of supporting cameras. Therefore, it was possible to migrate Augmented Reality to the mobile phones of everyday users. There isn't much data regarding the use of Augmented Reality in recreational Literature, but several studies have indicated that the use of this technology in schools helps and motivates students to read and understand texts, in addition to other positive impacts. Also, in the field of tourism, there are several studies that show that Augmented Reality is beneficial and that it attracts more people through, for example, the creation of online tourist guides, mainly in cultural heritage tourism. Therefore, it is intended to determine whether the use of Augmented Reality on mobile platforms can promote Tourism and Porto Poetry. To answer this question, a functional prototype was developed with several animated poems, related to various places in Porto. After its development, several people were invited to try the application, and several surveys were carried out where they questioned the user experience in relation to the application. The surveys also questioned through open questions, the relationships between Augmented Reality, Poetry, and Tourism and how they are promoted and communicate with each other.